2021
DOI: 10.3389/fpls.2021.768523
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt: An Essential Micronutrient for Plant Growth?

Abstract: Cobalt is a transition metal located in the fourth row of the periodic table and is a neighbor of iron and nickel. It has been considered an essential element for prokaryotes, human beings, and other mammals, but its essentiality for plants remains obscure. In this article, we proposed that cobalt (Co) is a potentially essential micronutrient of plants. Co is essential for the growth of many lower plants, such as marine algal species including diatoms, chrysophytes, and dinoflagellates, as well as for higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 210 publications
1
36
0
3
Order By: Relevance
“…62 In the case of Co, the specific mechanisms of plant uptake and transport inside the plant system are still unknown to a great extent, 13 but it is known that the Co 2+ form is absorbed by the plant roots. 6,13 Collins et al 5 assessed the Co uptake and translocation in tomato and wheat plants. The authors reported that Co in the roots is complexed with carboxylic acids, suggesting that Co could also be complexed with other organic ligands such as citrate or malate.…”
Section: Nanoparticle Characterization and Its Dissolution By The Eff...mentioning
confidence: 99%
See 4 more Smart Citations
“…62 In the case of Co, the specific mechanisms of plant uptake and transport inside the plant system are still unknown to a great extent, 13 but it is known that the Co 2+ form is absorbed by the plant roots. 6,13 Collins et al 5 assessed the Co uptake and translocation in tomato and wheat plants. The authors reported that Co in the roots is complexed with carboxylic acids, suggesting that Co could also be complexed with other organic ligands such as citrate or malate.…”
Section: Nanoparticle Characterization and Its Dissolution By The Eff...mentioning
confidence: 99%
“…3 Alternatively, Co has been described as a beneficial element, which means that low concentrations (0.01 to 10 mg kg −1 ) stimulate plant growth and yield, improve drought, salt, and heavy metal resistance, inhibit ethylene biosynthesis, and promote nitrogen fixation by increasing the number of nodules in legumes. [4][5][6] Iron and Co may be supplied in soluble chemical compounds to crops. 3 Chemical fertilizers containing these elements can enhance crop yield, but their excessive use in the long term may damage the soil microbial flora, disturb the soil mineral balance, and decrease the soil fertility.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations